Corporate lawyers and corporate governance - Loughrey, Joan , 1968- (International corporate law and financial market regulation, 2011)
"The role of corporate lawyers and their firms: the issues In 2010 a leading City law firm, Linklaters, attracted unwelcome media attention1 when the bankruptcy examiner?s report into the collapse of Lehman Brothers found that a legal opinion it had provided to its client had been used to mislead US authorities, although there was no suggestion that Linklaters itself had done anything wrong.2 The media interest was short-lived and gave rise to no broader debate about the role corporate law firms played for their corporate clients. In contrast, in the United States, even before Enron collapsed in 2000, there was lively debate on the subject of corporate lawyers and their corporate governance role"-- Provided by publisher